2022
DOI: 10.1093/bbb/zbac206
|View full text |Cite
|
Sign up to set email alerts
|

Small ruminant lentivirus capsid protein (SRLV-p25) antigenic structural prediction and immunogenicity to recombinant SRLV-rp25-coupled to immunostimulatory complexes based on glycyrrhizinic acid

Abstract: Small Ruminant Lentiviruses (SRLV) infect sheep and goats resulting in significant economic losses. This study evaluated for the first time the predicted conformational structure of the SRLV-capsid-protein 25 (SRLV-p25) and analysed the antigenicity of recombinant protein (SRLV-rp25) in mice by coupling to an immunostimulatory complexes based on glycyrrhizinic acid liposomes (GAL) and tested plasma from goats and sheep naturally infected. Analysis in silico and conformational structure of SRLV-p25 (genotype B-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The antibody response was dramatically higher using a Matrix-M TM as an adjuvant. Matrix-M TM selection was according to our research group [ 55 , 72 , 73 ]; we have observed that this immunostimulatory complex is an adjuvant that enhances strong immunogenicity using advanced technology in a nanocarrier to deliver antigens [ 59 ]. These results are in agreement with previously reported studies, which described antigen enhanced with Matrix-M TM as being highly immunogenic and inducing both antibody and cellular immune responses [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The antibody response was dramatically higher using a Matrix-M TM as an adjuvant. Matrix-M TM selection was according to our research group [ 55 , 72 , 73 ]; we have observed that this immunostimulatory complex is an adjuvant that enhances strong immunogenicity using advanced technology in a nanocarrier to deliver antigens [ 59 ]. These results are in agreement with previously reported studies, which described antigen enhanced with Matrix-M TM as being highly immunogenic and inducing both antibody and cellular immune responses [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A secondary antibody (mouse anti-IgG-HRP) was used with a dilution of 1:20,000. The chromogenic reaction was developed using 3,3′,5,5-tetramethylbenzidine (TMB) substrates (Sigma-Aldrich, St. Louis, MO, USA), as previously described [ 58 , 59 ] and measured at an absorbance of 450 nm. Statistical analyses were performed using two-way ANOVA to compare immunized groups with protein plus adjuvant versus protein alone on different days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were then centrifuged, pelleted, and solubilized in 5% N-lauroylsarcosine sodium salt and 50 mM Tris-HCl pH 7.5 (250 rpm, 12 h, 25 °C). rNTD-S were purified using immobilized-metal affinity chromatography (IMAC) according to the procedure described by Lara et al [ 29 ], it was dialyzed (Tris-HCl 5 mM, pH 8 buffer), quantified with the Bradford method [ 21 ], and confirmed by SDS-PAGE and WB before immunization of mice. Detection in WB was performed using anti-6x-His-Tag diluted 1:5000 (Invitrogen, Carlsbad, CA, USA) as primary antibody and a mouse anti-IgG conjugated to horseradish peroxidase (dilution 1:5000) (Sigma-Aldrich, St. Louis, MO, USA) as a secondary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…GA and its derivatives can form intermolecular complexes and micelles containing drug molecules for targeted delivery [ 18 , 19 ]. In addition, formulations based on phospholipids, cholesterol, and GA coupled with a viral antigen generated an increase in immune responses compared to the antigen alone, indicating that GA has promising effects if used within a vaccine antigen delivery system [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%